2020
DOI: 10.1103/physreve.101.012110
|View full text |Cite
|
Sign up to set email alerts
|

Bosons outperform fermions: The thermodynamic advantage of symmetry

Abstract: We examine a quantum Otto engine with a harmonic working medium consisting of two particles to explore the use of wave function symmetry as an accessible resource. It is shown that the bosonic system displays enhanced performance when compared to two independent single particle engines, while the fermionic system displays reduced performance. To this end, we explore the trade-off between efficiency and power output and the parameter regimes under which the system functions as engine, refrigerator, or heater. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 100 publications
4
61
0
Order By: Relevance
“…Regarding the possibility to exploit permutation symmetry for quantum technological prospects, we could mention for example some recent proposals commenting on thermodynamic advantages of bosonic over fermionic symmetry [27], or the role of mixed symmetries in the quantum Gibbs paradox [28,29]. The role of mixed symmetry in quantum computation and information theory also deserves our attention and will be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the possibility to exploit permutation symmetry for quantum technological prospects, we could mention for example some recent proposals commenting on thermodynamic advantages of bosonic over fermionic symmetry [27], or the role of mixed symmetries in the quantum Gibbs paradox [28,29]. The role of mixed symmetry in quantum computation and information theory also deserves our attention and will be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%
“…whereas the action of lowering operators S ij , i > j, is given by (26,27,30). From the definition (27) one can prove that…”
Section: U(l) Unirreps: Young Tableaux Gelfand Basis and Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, harmonic quantum Otto engines reach the Curzon-Ahlborn efficiency in the quasistatic limit [8,9]. More recently, it was demonstrated that the efficiency of endoreversible Otto engines at maximal power depends on the equation of state, i.e., the nature of the working medium [10][11][12][13][14] and the specific implementation of the power stroke [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In this cycle, the results of the efficiency depend on the nature of the working substance (through its energy spectrum) and the contributions of work and heat are separate in its stages, which facilitates theoretical modelling. These characteristics favor its extension to its quantum version, which has been studied extensively in recent years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%